Storage stability of pasteurized buco juice in pet bottles - Pamintuan, Evelyn R. (2002)
ABSTRACT Coconut water has gained popularity as a refreshing drink. In the Philippines, buko drinks available in the market are usually served in plastic cups exposed to contaminants that maybe harmful to the consumers. Most of them are not following the right handling and Good Manufacturing Process (GMP) needed for the safety of the product. To further improve the existing buko drinks, a study was conducted to pasteurize buko juice and determine storage stability in PET Bottle. Young coconuts of 7-8 months old in their Malakanin stage were used in buko juice mixed with refined white sugar and coconut meat. The coconut water taken from the coconut was diluted in three proportions (60:40, 70:30, 80:20) and subjected to sensory evaluation. Based on the results of Statistical Analysis by using ANOVA and DMRT at 5% level of significance, the ratio 80:20 at 7° Brix level of sweetness was the most acceptable coconut water-to-water ratio. The formulated buko juice was pasteurized at different time and temperature combinations (60°C for 5 min, 70°C for 2 min and 80°C for 5 sec). Based on sensory evaluation, 80°C for 5 sec was the most favored processing temperature that still maintains the flavor and freshness of the buko juice. The microbiological analysis also showed that heating buko juice at 80°C for 5 sec reduced the present of microorganisms compared to fresh buko juice. The pasteurized buko juice was then packed and sealed in PET bottles and stored under room temperature (15-35°C), freezing (-5°C) and refrigerated conditions (10-15°C). Freezing and refrigerated temperatures prolong the shelf-life of the buko juice for 3 weeks while normal room temperature lasts only for 2 days followed by the bulging of the PET